2018
DOI: 10.13187/ejced.2018.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and Assessing Cross-cultural Sensitivity in Bosnian Tertiary Education: Is there a real promise of harmonious coexistence?

Abstract: The aim of this research was to examine how university type, nationality, GPA, gender and grade level affect the cross-cultural sensitivity of students at tertiary level of education in Bosnia and Herzegovina. The revised and updated Inventory of Cross-Cultural Sensitivity (ICCSv2) was utilized for data collection. It contains four subscales: cultural inclusion, cultural behavioral integration, cultural anxiety, and cognitive flexibility. The representative sample consists of 219 students. The results have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Even though in academic settings females are more confident in their abilities to learn (Bećirović et al, 2018) a new language well (Dorneyi, 2001), a great number of research studies have shown that female students exhibit higher levels of anxiety than male counterparts (Abu-Rabia, 2004;Elkhafaifi, 2005), such results sometimes (Clark, Trafford, 1996) being attributed to the fact that female students are more likely to report their feelings of anxiety more openly than male students. In contrast to these, other enquiries found either no statistically significant genderrelated differences in language anxiety (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though in academic settings females are more confident in their abilities to learn (Bećirović et al, 2018) a new language well (Dorneyi, 2001), a great number of research studies have shown that female students exhibit higher levels of anxiety than male counterparts (Abu-Rabia, 2004;Elkhafaifi, 2005), such results sometimes (Clark, Trafford, 1996) being attributed to the fact that female students are more likely to report their feelings of anxiety more openly than male students. In contrast to these, other enquiries found either no statistically significant genderrelated differences in language anxiety (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relevance of this study is to raise the College of Teacher Education students' ability to reduce cultural barriers between cultures they interact. Education students need to consider how cultural variations impact people's interactions and establish exceptional views, personalities, and relations with others [20]. Students need to be taught how to build favorable treatment towards people from different cultures with diverse cultural values.…”
Section: Introductionmentioning
confidence: 99%
“…They contain culturally responsive content and serve as excellent tools for the development of cultural intelligence. Students can learn about diverse cultures from various locations in Bosnia and Herzegovina and from around the world (Bec´irovic´& Brdarevic´-cˇeljo, 2018). Cultural intelligence (CQ) may assist in the development of positive relationships and success in culturally diverse settings.…”
Section: Introductionmentioning
confidence: 99%